Flotation separation of fluorite from calcite using polyaspartate as depressant. (May 2018) - Zhu, Hailing; Qin, Wenqing; Chen, Chen; Chai, Liyuan; Jiao, Fen; Jia, Wenhao
Highlights: PASP exhibits excellent selective inhibition for calcite flotation. A concentrate containing 93.56% CaF2 with a recovery of 57.82% is obtained. PASP and NaOL can adsorb on fluorite and calcite surface at pH 7–8. The addition of PASP prevent the adsorption of NaOL on calcite surface. Abstract: Flotation separation of carbonate fluorite ore is a puzzle in mineral processing. In this study, the flotation separation of fluorite from calcite using polyaspartate (PASP) as depressant and sodium oleate (NaOL) as collector was investigated, and the adsorption mechanism was analyzed by zeta potential measurement and infrared spectrum (IR) analysis. Flotation results show that NaOL exhibits excellent collecting performance to fluorite and calcite. Moreover, PASP addition can selectively inhibit calcite. A concentrate containing 93.56% CaF2 with a recovery of 57.82% is obtained in the closed-circuit flotation experiment on the real ore. Zeta potential measurement and IR analysis results indicate that both PASP and NaOL can adsorb on fluorite and calcite surface individually. Additionally, the adsorption of PASP can hinder the adsorption of NaOL on calcite surface but exert little influence on the adsorption of NaOL on fluorite surface. Therefore, PASP is an effective depressant for flotation separation of fluorite from calcite.